THE INFLUENCE OF THE FAMILY ENVIRONMENT AND SELF-REGULATED LEARNING ON STUDENT LEARNING OUTCOMES - Astuti, Rima Fuji; Sudiarditha, I Ketut R.; Pratama, Aditya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This research was conducted to determine how much influence the family environment and self-regulated learning had on student learning outcomes. This research was conducted at SMA Negeri 21 Jakarta using the survey method, where the questionnaire became the research instrument. This study used quantitative data using regression analysis and the processing of the data was analyzed using SPSS. The population in this study were all students of class XI Social Studies at SMA Negeri 21 Jakarta for the 2021/2022 Academic Year, a total of 160 students. The sample used is Saturated Sample, which is a sampling technique when all members of the population are sampled, meaning that the sample in this study is 160 students. The results of this study are family environment has a positive effect on student learning outcomes; self-regulated learning has a positive effect on student learning outcomes, and; family environment and self-regulated learning has a positive effect on student learning outcomes.